Социология восточноевропейского города I тыс. до н. э. (по материалам Бельского городища и Ворсклинской региональной системы скифского времени) - Бойко, Ю. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary BoykoYu. N. Sociology of an East-European City of the First Millenium BC (According to the Materials on Excavations at the Belsk Site of an Ancient Town and the Vorsjda-River Regional System Dated to the Scythian Times) The article considers the Vorskla river regional system oi Scythian times with the town of Gclon being its kernel. I he defined type of the surrounding area organization system is characteristic lor town-states at the early class stage1. The analysis of excavations of the estates in the sites of ancient towns and settlements yields a conclusion that ancient society that inhabited the Vorskla river regional system had a developed estate and caste structure.